Taxation of Islamic Finance (IF) and Its Exposure to Tax Costs under Ethiopian Tax Law - Jarra, Kassim Kuffa (Bahir Dar University Journal of Law, 2024)
The uncertainty of the rule applicable for the taxation of Islamic finance (IF) causes vulnerability to cumbersome tax cost or tax avoidance risks. Stakeholders blame Ethiopian tax law for the differential tax treatment of IF and conventional bank (CB), exposing beneficiaries of IF to intermediary taxes (twice stamp duty - on purchase and resale) in trade intermediation services, triple in sharia compliant bond (sukuk), and denial of the deduction of financial costs. An article aims to examine the tax treatment of IF returns, intermediary activity, exemption and the deductibility of financing costs for IF. It has utilized a doctrinal research design which is limited to the analysis of law, secondary sources and some primary data. Specifically, it uses a comparative qualitative approach drawing lessons from Malaysian, the UK and SA because such jurisdictions have experience regarding tax treatment of IF transactions. The finding indicates that the Ethiopian tax law is silent on deductible IF costs, intermediary activities and whether or not IF returns are subject to corporate income, dividend and interest income taxes. The 2016 tax law allows deduction of interest cost for CB loans and denies deduction of equity finance costs (dividend) exposing IF for cumbersome costs. Thus, the silence of tax law, lack of a playing tax field for IF and CB and the law‟s denial of deduction denial to IF expose latter to higher costs and unsustainability. Thus, the Ethiopian tax law needs to be revisited in light of the equal tax treatment of IF and CB.